2014
DOI: 10.1080/03632415.2013.836500
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Urban Water Body Challenges and Approaches: (1) Rehabilitation and Remediation

Abstract: published scientific literature and what is known and needed by professionals actively working to rehabilitate aquatic resources in Oregon urban and rural residential areas. IMST (2012) summarized what was learned at that workshop and stimulated these two Fisheries articles, as well as a book (Yeakley et al., 2014).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 104 publications
0
34
0
4
Order By: Relevance
“…For example, in stream ecology, the so called urban stream syndrome has gained much research interest in the past 15 years (Paul and Meyer 2001;Meyer et al 2005;Walsh et al 2005;Hughes et al 2014). This concept identifies a number of factors that affect urban watercourses that lead to reductions in biodiversity and dominance of tolerant species: increases in water-level fluctuation, nutrients, pollutants, temperature, and canalisation (Walsh et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in stream ecology, the so called urban stream syndrome has gained much research interest in the past 15 years (Paul and Meyer 2001;Meyer et al 2005;Walsh et al 2005;Hughes et al 2014). This concept identifies a number of factors that affect urban watercourses that lead to reductions in biodiversity and dominance of tolerant species: increases in water-level fluctuation, nutrients, pollutants, temperature, and canalisation (Walsh et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrologically, it is well established that increases in impervious cover, coupled with drainage systems in urban areas, create a flashier hydrological regime; for example, a study of nine urban areas dispersed across the United States showed a consistent pattern of increased magnitude and frequency of high flow events associated with urbanisation (Brown et al, 2009). Whilst this trend is well documented in temperate regions, evidence from Puerto Rico, where rivers are naturally flashy due to the precipitation regime and catchment characteristics, indicated that urban river regimes did not differ from naturally forested catchments , highlighting the need for further research in other ecoregions (Hughes et al, 2014b). Urbanisation can also modify the hydrological regime at the other end of the continuum via a reduction in base flows (Wenger et al, 2009), aquatic connectivity (Kaushal and Belt, 2012), and sediment delivery and transport (Taylor and Owens, 2009) resulting in changes to channel morphology (Chin, 2007).…”
Section: Ecosystem Responses To Urbanisationmentioning
confidence: 99%
“…Whilst an understanding of ecosystem responses to urbanisation is reasonably well established, further research on the impacts of urbanisation on habitat connectivity is required (Hughes et al, 2014b). Existing research has also tended to focus on specific geographic areas / regions and on relatively small catchments or waterbodies.…”
Section: Contributions and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation and remediation of these urban bayous would also improve these unique ecosystems and increase ecosystem services such as fishing and clean water (Hughes et al 2014).…”
Section: Expectationsmentioning
confidence: 99%